Hybridization of additive manufacturing processes to build ceramic/metal parts: Example of LTCC. Issue 3 (March 2020) - Raynaud, Jonathan; Pateloup, Vincent; Bernard, Mégane; Gourdonnaud, Delphine; Passerieux, Damien; Cros, Dominique; Madrangeas, Valérie; Chartier, Thierry
Abstract: Stereolithography is an additive manufacturing process which makes it possible to fabricate useful complex 3D ceramic parts with a high dimensional resolution and a good surface finish. By coupling the latter process with a second, to deposit an other material, it will be possible to obtain multi-material parts using a hybrid machine. This machine is therefore composed of two additive manufacturing processes: stereolithography and robocasting. During this work, we decided to study ceramic - metal assemblies and more particularly the LTCC materials. These materials have low sintering temperatures, generally less than 1000 °C. The mechanical and electrical properties will be studied of the development of parts with complex and innovative geometries to improve the characteristics of current circuits. Finally, our substrate have an excellent permittivity (εr  = 5.05) and dielectric loss (tan δ = 1.8.10 −3 ).